Brief communication: The Khurdopin glacier surge revisited – extreme flow velocities and formation of a dammed lake in 2017 - J. F. Steiner; P. D. A. Kraaijenbrink; S. G. Jiduc; W. W. Immerzeel (The Cryosphere, 2018)
Glacier surges occur regularly in the Karakoram, but the driving mechanisms, their frequency and its relation to a changing climate remain unclear. In this study, we use digital elevation models and Landsat imagery in combination with high-resolution imagery from the Planet satellite constellation to quantify surface elevation changes and flow velocities during a glacier surge of the Khurdopin Glacier in 2017. Results reveal that an accumulation of ice volume above a clearly defined steep section of the glacier tongue since the last surge in 1999 eventually led to a rapid surge in May 2017 peaking with velocities above 5000 m a−1, which were among the fastest rates globally for a mountain glacier. Our data reveal that velocities on the lower tongue increase steadily during a 4-year build-up phase prior to the actual surge only to then rapidly peak and decrease again within a few months, which confirms earlier observations with a higher frequency of available velocity data. The surge return period between the reported surges remains relatively constant at ca. 20 years. We show the potential of a combination of repeat Planet and ASTER imagery to (a) capture peak surge velocities that are easily missed by less frequent Landsat imagery, (b) observe surface changes that indicate potential drivers of a surge and (c) monitor hazards associated with a surge. At Khurdopin specifically, we observe that the surging glacier blocks the river in the valley and causes a lake to form, which may grow in subsequent years and could pose threats to downstream settlements and infrastructure in the case of a sudden breach.